2011
DOI: 10.1111/j.1948-7134.2011.00131.x
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of resting and breeding habitats of adult sand flies in the Judean Desert

Abstract: Recently, in several areas of the Middle East, a sharp increase of cutaneous leishmaniasis was observed in suburbs of larger towns including Jerusalem. In some of these areas, poor housing conditions and unsuitable waste management was suspected to provide ideal conditions for sand fly breeding, but hard data on diurnal resting sites and breeding habitats of most sand fly species are scant. In this study, we chose 16 sites on both slopes and the bottom of a natural valley in the Judean Desert to conduct a surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 37 publications
2
11
1
2
Order By: Relevance
“…Our efforts failed to capture any sand flies emerging from soil in valley floors or slopes with or without vegetation or stones. These differing findings may be due to the fact that Muller et al [27] were dealing primarily with Ph tobbi and Ph major while our study and that of Orshan et al [21] focused on Ph. sergenti .…”
Section: Discussioncontrasting
confidence: 58%
See 3 more Smart Citations
“…Our efforts failed to capture any sand flies emerging from soil in valley floors or slopes with or without vegetation or stones. These differing findings may be due to the fact that Muller et al [27] were dealing primarily with Ph tobbi and Ph major while our study and that of Orshan et al [21] focused on Ph. sergenti .…”
Section: Discussioncontrasting
confidence: 58%
“…Interestingly, other studies performed in the Judean Desert suggested sand fly breeding and resting occurs primarily in valley floors covered with vegetation [27]. Our efforts failed to capture any sand flies emerging from soil in valley floors or slopes with or without vegetation or stones.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…For example, the transmission of leishmaniasis formerly occurred over wide areas from where it has now been eliminated by agricultural development and insecticide treatment. It is known that in relation to rice cultivation, mechanization is likely to be associated with increased flooding and scant vector breeding opportunities (Hunter, 2003;Müller et al, 2011). Moreover, agricultural practices can cause the local extirpation of reservoir hosts, such as the destruction of gerbil habitats (Moškovskij and Duhanina, 1971).…”
Section: Sample Sitementioning
confidence: 99%